Long-Term Mortality and Morbidity Related to Congestive Heart Failure with Reduced Ejection Fraction (CHFrEF) in Palestinian Patients Maintained on Submaximal Sacubitril/Valsartan Doses: A Pilot Study - Aqel, Raed; Alzughayyar, Tareq Z.; Abukhalaf, Sadi A.; Misk, Rami A.; Zalloum, Jihad Samer (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Background. The efficacy of sacubitril/valsartan, a newly introduced combination drug for heart failure with reduced ejection fraction (HFrEF), was demonstrated in the PARADIGM-HF trial conducted in Western countries. However, these findings need to be verified in the Middle Eastern context, where patients may exhibit a different response due to different environmental and racial factors. Objectives. The goal of this study was to evaluate the efficacy of submaximal sacubitril/valsartan doses in terms of improving the disease symptoms, as measured by the New York Heart Association (NYHA) classification and left ventricular ejection fraction (LVEF) percentage, as well as establish long-term morbidity and mortality associated with HFrEF among Palestinian patients administered target doses of an angiotensin-converting enzyme inhibitors (ACEI) or angiotensin II receptor blockers (ARBs). Material and Methods. This study involved a retrospective review of charts related to patients with HFrEF maintained on sacubitril/valsartan and was conducted in a referral cardiology clinic in Palestine. The inclusion criteria were age 18+, HFrEF diagnosis, sacubitril/valsartan usage for at least six months during the period between January 1, 2016, and June 30, 2019, and LVEF<40%. The exclusion criteria included LVEF≥40% and drug administration duration<6 months. The collected data included NYHA class, as well as LVEF, serum sodium (Na), potassium (K), serum creatinine (Cr), and blood urea nitrogen (BUN) levels and the mortality rate before and after the minimum treatment duration. IBM SPSS STATISTICS for Windows, version 20.0, Armonk, NY: IBM Corp. IBM Corp., released 2012, was used for data analysis, whereby T score was calculated for comparisons between numerical groups, and p<0.05 was considered statistically significant. Results. The initial study sample comprised of 205 consecutive patients with HFrEF maintained on sacubitril/valsartan for at least six months from January 1, 2016, to June 30, 2019. Three patients were excluded due to attrition, along with further 12 patients with LVEF≥40% (based on the PARADIGM-HF trial criteria). Throughout the treatment period, most patients showed escalating improvement in terms of the LVEF and NYHA classification, as LVEF=29.8% and NYHA=3 were obtained on average before initiating sacubitril/valsartan, compared to 41% and 1.7, respectively, after 6-month treatment (p=0.0003 and 0.046, respectively). These improvements in LVEF and NYHA class were noted across all sacubitril/valsartan doses (50−400 mg). However, 23 patients (12%) died while undergoing sacubitril/valsartan treatment. Conclusion. A significant long-term reduction in the mortality and morbidity rates was observed in Palestinian patients with HFrEF maintained on submaximal doses of sacubitril/valsartan.